The academic and non-academic factors related to students' attrition and or subject failing at the sociology Departament of the School of Arts and Sciences of the University of El Salvador, semester 1-2000 - Alas Portillo, Ana Silvia; Mena Domínguez, Waldo Miguel; Vásquez, Marcos Antonio; Blandón de Castro, Norma Cecilia (San Salvador : Universidad de El Salvador, 2002)
Nowadays, the students’ subject failing and attrition constitute problems for educational institutions at any level. So new academic advising program and new teaching methodologies have been put into practice in order to control these phenomena. According to “La Direccion General de Evaluacion de Calidad Educativa” from Honduras, the causes that are closely related to subject failing are linked to several factors such as the teaching learning process, the system of evaluation and the students themselves who don’t want to study. In addition to this, according to Dr. Badia Sierra, Director of the planning office of the University of El Salvador (UES), when interviewed on May 17th, 2001, the UES as a tertiary educational institution faces this problem. He said that the attrition problem is the result of different causes such as: lack of students’ academic preparation, students’ emotional problems, students’ entrance profile, maturity, lack of teaching materials, teachers’ lack of interest in the teachinglearning process. He said that due to all these reasons, a great number of students of the UES quit their studies.
Incluye anexos
Tesis (Licenciatura en Idiomas opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2002
Keywords: Rendimiento académico bajo